Rationalitätsdefizite in der Biopolitik - Kauffmann, Clemens (Politische Vierteljahresschrift, 2008)
The progress of molecular medicine and bio technology has become a fundamental focal point for society as a whole. Ethical and political assessments of bio medical developments remain difficult. On the one hand these are subject to political and legal measures, on the other hand one talks about political abuse", a scaring ethicism in research policies or a frightening politicization of the bio ethical debate, respectively. The difficulties that emerge during the transfer of scientific expertise and moral convietions into bio-political norms prove to be symptoms of wide-ranging rationality deficits in bio politics. They can be deduced from political semantics in the border-regions of bio medical research, ethical evaluation, political direction and political analysis. In this context, certain adaptations of "public reason" and discourse models, which show rationality deficits on their terms, have to be judged critically. A problem here is a common reservation against certain approaches of political philosophy. However, because of the crucial deficits with regard to the explication of bio political principles and fundamental issues pertaining to democratic theory, political philosophy can serve as a "rationality reserve".
UnivIS-Import:2015-03-09:Pub.2008.phil.dsp.ipowi.lpowi2.ration
Keywords: Bioethics; Biopolitics; Enquete committee; Political philosophy; Public reason